Redox Systems Under Nano-Space Control - Hirao, Toshikazu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
The generation of novel redox systems under nano-space control is one of the most exciting fields in present organic, inorganic, and supramolecular chemistry. The authors have drawn together the newest information on the construction of such novel redox systems using nano-space control of complexation or molecular chain-induced spaces and metal- or self-assembled spaces through combining techniques in coordination, supramolecular, and bio-inspired chemistry. Such design on the nano level produces hybrid conjugated systems composed of transition and synthetic metals, metallohosts, redox-active self-assembled monolayers of helical peptides, DNA-directed metal arrays, photoactive antibody systems, chiral rotaxanes, and redox-active imprinted polymers. In the future, these systems will be the basis for novel selective electron-transfer reactions as well as new functional materials and catalysts.
Redox Systems via d,?-Conjugation -- Conjugated Complexes with Quinonediimine Derivatives -- Realizing the Ultimate Amplification in Conducting Polymer Sensors: Isolated Nanoscopic Pathways -- Metal-Containing ?-Conjugated Materials -- Redox Active Architectures and Carbon-Rich Ruthenium Complexes as Models for Molecular Wires -- Molecular Metal Wires Built from a Linear Metal Atom Chain Supported by Oligopyridylamido Ligands -- Multielectron Redox Catalysts in Metal-Assembled Macromolecular Systems -- Redox Systems via Coordination Control -- Triruthenium Cluster Oligomers that Show Multistep/Multielectron Redox Behavior -- Molecular Architecture of Redox-Active Multilayered Metal Complexes Based on Surface Coordination Chemistry -- Programmed Metal Arrays by Means of Designable Biological Macromolecules -- Metal-Incorporated Hosts for Cooperative and Responsive Recognition to External Stimulus -- Synthesis of Poly(binaphthol) via Controlled Oxidative Coupling -- Redox Systems via Molecular Chain Control -- Nano Meccano -- Through-Space Control of Redox Reactions Using Interlocked Structure of Rotaxanes -- Metal-Containing Star and Hyperbranched Polymers -- Electronic Properties of Helical Peptide Derivatives at a Single Molecular Level -- Construction of Redox-Induced Systems Using Antigen-Combining Sites of Antibodies and Functionalization of Antibody Supramolecules.
Keywords: Nanotechnology; Inorganic chemistry; Polymers .; Organometallic chemistry .; Catalysis; Organic chemistry; Nanotechnology; Inorganic Chemistry; Polymer Sciences; Organometallic Chemistry; Catalysis; Organic Chemistry